Penerapan model pembelajaran fun learning dalam meningkatkan hasil belajar menulis karangan narasi siswa sekolah dasar - Rezki Aulia Syukri; Aliem Bahri; Ummu Khaltsum (Educational and Talent Development Center of Indonesia, 2021)
The main problem in this study is whether the application of the fun learning model can improve the skills of writing narrative essays in the fifth-grade students of UPT SPF SD Inpres Parang Makassar City. This study aims to find out how the application of the fun learning model in improving narrative essay writing skills in class V UPT SPF SD Inpres Parang Makassar City. This type of research is class action research (Class Action Research) which consists of two cycles where each cycle is carried out four times. The focus of this research is 1) narrative essay writing skills and 2) the use of fun learning models in class V UPT SPF SD Inpres Parang Makassar City. The research procedure includes planning, implementing actions, observing, and reflecting. The research subjects were students of class V, totaling 16 people. The data collected were analyzed using quantitative and qualitative analysis. The results of this study are: (1) In the first cycle, the average value of student learning outcomes for Class V UPT SPF SD Inpres Parang Makassar City is 58.7 (2) In the second cycle, the average value of student learning outcomes for class V UPT SPF is obtained. Inpres Parang Elementary School in Makassar City was higher at 82.5. The learning completeness of the fifth-grade students of UPT SPF SD Inpres Parang Makassar City has also increased. In the first cycle, from 3 (18.7%) students achieved complete learning, while in the second cycle, 14 (87.5%) students achieved learning mastery, and classical learning mastery was achieved. This means that learning completeness in cycle II is achieved classically because the number of students who complete is more than 85%.